Repellency and Composition of Essential Oils of Selected Ethnobotanical Plants Used in Western Kenya against Bites of Anopheles gambiae Sensu Stricto. Issue 3 (3rd May 2020) - Ywaya, David O.; Birkett, Michael A.; Pickett, John A.; Ochola, John B.; Wilber, Lwande; Wachira, Benson M.; Hassanali, Ahmed; Ng'ang'a, Margaret M.
Abstract: The essential oils of Ocimum gratissimum Linn, Hyptis suaveolens (L) Poit and Vitex keniensis, which are used traditionally in Western Kenya for personal and space protection against mosquito bites, were screened for repellence against Anopheles gambiae Sensu Stricto. Essential oils were extracted from their leaves by hydrodistillation, characterised by gas chromatography linked with mass spectrophotometer and electroantennogram detectors. The repellency of the oils and their selected blends was studied by the reduction in probing and feeding on the human arm. The oils showed promising repellency for Anopheles gambiae, O. gratissimum (RD50 = 2.77 × 10 -5 mg cm -2, 95% CI), Vitex keniensis (RD = 5.68 × 10 -5 mg cm -2 ) and Hyptis suaveolens (6.27× 10 -5 mg cm -2 ) as compared to that of DEET (control) RD = 1.25×10 -5 mg cm -2 ). The bioactive constituents of each oil were identified by Gas chromatography-linked with Mass spectrometry and Electroantennography. Some compounds were confirmed by co-injections of the oil with available authentic standards. The results provide a scientific rationale for the traditional use of these plants in repelling disease vectors and other biting insects, and lay down some useful groundwork for downstream development of more effective products for personal and space protection.